Diagnostic approach to limbal stem cell deficiency - Daniella Lent-Schochet; Mizna Akbar; Joshua H. Hou; Asim V. Farooq (Frontiers in Ophthalmology)
Limbal stem cell deficiency (LSCD) is an important cause of visual and ocular morbidity. Effective diagnosis and management require a thoughtful and comprehensive evaluation of the ocular surface. This review describes the pathogenesis, diagnosis, and grading of LSCD, as well as characteristic findings via slit lamp examination, in-vivo confocal microscopy, anterior segment optical coherence tomography (AS-OCT), impression cytology, and OCT angiography.